A lean bioabsorbable magnesium-zinc-calcium alloy ZX00 used for operative treatment of medial malleolus fractures: early clinical results of a prospective non-randomized first in man study. Issue 8 (1st August 2020) - Holweg, Patrick; Herber, Valentin; Ornig, Martin; Hohenberger, Gloria; Donohue, Nicolas; Puchwein, Paul; Leithner, Andreas; Seibert, Franz
Abstract : Aims: This study is a prospective, non-randomized trial for the treatment of fractures of the medial malleolus using lean, bioabsorbable, rare-earth element (REE)-free, magnesium (Mg)-based biodegradable screws in the adult skeleton. Methods: A total of 20 patients with isolated, bimalleolar, or trimalleolar ankle fractures were recruited between July 2018 and October 2019. Fracture reduction was achieved through bioabsorbable Mg-based screws composed of pure Mg alloyed with zinc (Zn) and calcium (Ca) ( Mg-Zn0.45-Ca0.45, in wt.%; ZX00). Visual analogue scale (VAS) and the presence of complications (adverse events) during follow-up (12 weeks) were used to evaluate the clinical outcomes. The functional outcomes were analyzed through the range of motion (ROM) of the ankle joint and the American Orthopaedic Foot and Ankle Society (AOFAS) score. Fracture reduction and gas formation were assessed using several plane radiographs. Results: The follow-up was performed after at least 12 weeks. The mean difference in ROM of the talocrural joint between the treated and the non-treated sites decreased from 39° (SD 12°) after two weeks to 8° (SD 11°) after 12 weeks (p ≤ 0.05). After 12 weeks, the mean AOFAS score was 92.5 points (SD 4.1). Blood analysis revealed that Mg and Ca were within a physiologically normal range. All ankle fractures were reduced and stabilized sufficiently by two Mg screws. A complete consolidation of all fractures was achieved. No loosening or breakage of screws was observed. Conclusion: This first prospective clinical investigation of fracture reduction and fixation using lean, bioabsorbable, REE-free ZX00 screws showed excellent clinical and functional outcomes. Cite this article: Bone Joint Res 2020;9(8):477–483.